CodY Is a Global Transcriptional Regulator Required for Virulence in Group B Streptococcus - Pellegrini, Angelica; Lentini, Germana; Famà, Agata; Bonacorsi, Andrea; Scoffone, Viola Camilla; Buroni, Silvia; Trespidi, Gabriele; Postiglione, Umberto; Sassera, Davide; Manai, Federico; Pietrocola, Giampiero; Firon, Arnaud; et al. (Frontiers in Microbiology, 2022)
Group B Streptococcus (GBS) is a Gram-positive bacterium able to switch from a harmless commensal of healthy adults to a pathogen responsible for invasive infections in neonates. The signals and regulatory mechanisms governing this transition are still largely unknown. CodY is a highly conserved global transcriptional regulator that links nutrient availability to the regulation of major metabolic and virulence pathways in low-G+C Gram-positive bacteria. In this work, we investigated the role of CodY in BM110, a GBS strain representative of a hypervirulent lineage associated with the majority of neonatal meningitis. Deletion of codY resulted in a reduced ability of the mutant strain to cause infections in neonatal and adult animal models. The observed decreased in vivo lethality was associated with an impaired ability of the mutant to persist in the blood, spread to distant organs and cross the blood-brain barrier. Notably, the codY null mutant showed reduced adhesion to monolayers of human epithelial cells in vitro and an increased ability to form biofilms, a phenotype associated with strains able to asymptomatically colonize the host. RNA-seq analysis showed that CodY controls about 13% of the genome of GBS, acting mainly as a repressor of genes involved in amino acid transport and metabolism and encoding surface anchored proteins, including the virulence factor Srr2. CodY activity was shown to be dependent on the availability of branched-chain amino acids, which are universal co-factors of this regulator. These results highlight a key role for CodY in the control of GBS virulence.